PHILOSOPHICAL-THEORETICAL FOUNDATIONS OF THE STUDY OF THE PHENOMENON OF UNDERSTANDING NATIONAL IDENTITY - Saparova, Gulbakhar Aytbaevna (SCIENCE and SOCIETY, 2026)
The article discusses issues of national identity. In addition, concepts such as unity, kindness, clan-tribal relations, religious beliefs, and national values are described. Also, scholars emphasize the commonality of mind and morals, and by forming the spirituality of each person and nation, the formation of national characteristics and national values and self-awareness are given a special place.